L’écriture autobiographique chez François-René de Chateaubriand Dans les Mémoires d’outre-tombe (Journal of the College of Basic Education, 2023)
It is difficult to realize the theme of the writer in some of the literary works such as « After death Memoirs » by Chateaubriand because the writer himself is a good representative of his age .writing biography of a writer is considered a hard work because writing doesn’t transfer the identity of the writer clearly besides the literary text has an unrealistic dimensioneven if the events narrated in the text are real.In an attempt to present exquisite writings to his readers ,Chateaubriand consider the value of literary work as more superior than the reality of its events.«After death memoirs» can hardlyPresent the idea of ego because of its value and the unique methods of expression.The attitude of Chateaubriand towards writing biography is interesting because «After death memoirs» is considered as a continuous project although it may submit to the continuous changes of the writer .the biography of Chateaubriand exceeds the limits of his personalityAnd includes France and its future ,this gave Chateaubriand a chance to make a comparison Where the writer presents his literary mediations. Writing biography makes it necessary forThe writer to ask about the theme behind writing .In fact biography is an example of meditation because the writer asks himself about the reasons which led him to attract the attention of the readers to his destiny.At the end of the «After death memoirs » Chateaubriand devoted himself to presume his literary project as heFinished his memoirs at the age of 73.Chateaubriand wanted to achieve a victory againstTime by death besides he succeeded in creating the immortality in order to keep himself Immortal even after death